To evaluate customer needs and satisfaction at UUM Parcel Centre Using Kano Model - Abdul Wahab, Abdul Muiz; Asaad, Mohamad Norhasni (Universiti Utara Malaysia, 2020)
The purpose of this study is to describe customer satisfaction assessment based on customer needs at UUM Parcel Center using Kano Model method. In addition, the purpose of this study is to identify the dimension of customer needs in Kano Model categories. It using quantitative research methods, data were collected through questionnaires. Respondents included 313 STML students but returned a questionnaire of 122 students. For successful operations, understanding customer needs and satisfaction is very important in identifying the facilities and services provided by UPC. The relationship between customer needs and customer satisfaction will impact organizational performance. In this study we used the Kano model to analyze customer needs and satisfaction for the future success of UUM Parcel Center. The results show that students at STML are more likely to be satisfied with the dimensions of customer needs and need to prioritize aspects of facilities and service dimensions. The understanding of customer needs and satisfaction is very important in the design of products and services. At same time, the Kano model can be applied in product development and service performance.